Child care for low-income families : summary of two workshops - Phillips, Deborah A. (National Academy Press, 1995)
Child care has become a fact of life for American families. Most children now enter child care during the first year of life and spend a substantial amount of time prior to school entry in the care of adults other than their parents. The implications of this profound shift in childrearing for children's health and safety, emotional security, and preparation for school are far-reaching. Child care also lies at the core of current debates about welfare reform and school readiness, and so it has moved to center stage in the larger arena of discussion about federal policy for children and families. What does research now tell us about patterns of child care use among low-income families and the factors that affect these patterns? What is the range of quality that characterizes today's child care arrangements, with what effects on children? What is known about the role of child care in families' efforts to prepare for and maintain paid employment? What are the local impacts of federal child care subsidies? What role are they playing in families' efforts to find affordable child care that also safeguards the security and well-being of their children?